Asimilasi Budaya dan Agama: Menelusuri Jejak Teori Gujarat di Pesisir Indonesia dan Malaysia - Dwi Nisrina Khumairoh; Kholid Mawardi (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
An adaptive and peaceful socio-cultural approach characterizes the Islamization process in the Malay-Indonesian Archipelago. Among various historical theories, the Gujarat Theory offers a robust sociological explanation regarding the moderate character of early Islam in coastal regions. This study aims to analyze the cultural and religious assimilation and trace the remaining manifestations of the Gujarat Theory in shaping comparative religious traditions across the maritime coasts of Indonesia and Malaysia. The research method employed is a literature study (library research) with a qualitative-comparative approach. Data analysis was conducted using content analysis and source triangulation of historical literature. The study reveals three main findings. First, the spread of Islam was driven by the flexible Sufi practices of Gujarati merchants, which made it easily accepted by local communities. Second, coastal areas acted as cosmopolitan gateways that transmitted Islamic values through trade and marriage, establishing the Sultanates of Samudera Pasai and Malacca. Third, this assimilation is materially evidenced by the identical architecture of ancient gravestones from Cambay found in Aceh and Malaysia, and non-materially by the daily religious rituals of coastal communities. This study concludes that coastal Islam in Indonesia and Malaysia shares a common, inclusive, and moderate spiritual and cultural genealogical root.   Keywords: Coastal Communities, Cultural Assimilation, Gujarat Theory, Indonesia-Malaysia, Maritime Sufism